From Ovid to COVID - Desmond Manderson (Law Text Culture, 2022)
We get the metaphors we deserve. On the one hand this essay explores, in the shadow of Susan Sontag, the meanings and implications of the metaphorical language that was deployed by state and society to understand COVID-19 and to regulate our response to it. On the other hand it argues that the pandemic is not so much a metaphor as a metamorphosis: not a sign of something new but a symptom of something that has already taken place, a profound transformation that appears dramatic only if you have failed to notice the underlying compounds that, like a witch’s brew, have been slowly bubbling away all along. The 2020s revealed with new clarity the forces of neoliberalism that have been eating away at the roots of our societies for thirty years. Social distance, working from home, the gig economy, new limits on civil society. All these underlying socio-political aspects of the neoliberal social contract were brought into sharp relief. Yet a crisis is not an epilogue but a moment of decision. It may be then, that the very visibility that COVID-19 has rendered these underlying forces provides us with an opportunity to reconsider them. If nothing else, the experience of COVID-19 has clarified the ways in which our self-interest, economic and psychological, depends on the welfare of others; the ways in which the economic prosperity and standard of living of each of us relies on a whole range of public goods from higher education and universal health care to decent welfare systems to affordable child care. If the metaphor of the lockdown turns out to signify a dies non for reflection or to catch our breath, it will have been worth it after all.